2019
DOI: 10.1071/rd18444
|View full text |Cite
|
Sign up to set email alerts
|

IVM of mouse fully grown germinal vesicle oocytes upon a feeder layer of selected cumulus cells enhances their developmental competence

Abstract: In the ovary, acquisition of oocyte developmental competence depends on a bidirectional exchange between the gamete and its companion cumulus cells (CCs). In this study we investigated the contribution of CCs surrounding oocytes of known developmental competence or incompetence to the acquisition of oocyte developmental competence. To this end, feeder layers of CCs (FL-CCs) were prepared using CCs isolated either from: (1) developmentally competent mouse oocytes whose nucleolus was surrounded by a chromatin ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…To this end, we employed a number of known cytological quality markers of the meiotic division to compare MI or MII oocytes matured in vitro, either in the absence or in the presence of 1 nM 2-OHE 2 , and those obtained by ovulation. Specifically, we analysed (i) the PB-I volume [6,[34][35][36][37][38][39][40][41][42][43] and its position in respect to the oocyte's spindle [44]; (ii) the presence and extension of the cortical F-actin cap [45][46][47]; (iii) the meiotic spindle shape and area [48][49][50][51] and (iv) the microtubule organisation centre (MTOC) localisation [8,48,52].…”
Section: Blastocyst Cell Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we employed a number of known cytological quality markers of the meiotic division to compare MI or MII oocytes matured in vitro, either in the absence or in the presence of 1 nM 2-OHE 2 , and those obtained by ovulation. Specifically, we analysed (i) the PB-I volume [6,[34][35][36][37][38][39][40][41][42][43] and its position in respect to the oocyte's spindle [44]; (ii) the presence and extension of the cortical F-actin cap [45][46][47]; (iii) the meiotic spindle shape and area [48][49][50][51] and (iv) the microtubule organisation centre (MTOC) localisation [8,48,52].…”
Section: Blastocyst Cell Numbermentioning
confidence: 99%
“…The importance to preserve the communication between oocyte and surrounding granulosa cells becomes evident when cumulus-oocyte complexes (COCs) are isolated from fully grown antral follicles and in vitro cultured [ 3 , 4 ]. In the mouse, the efficiency of COCs in vitro maturation (IVM) varies depending on both strain (i.e., outbred or inbred) [ 5 ] and culture conditions [ 6 , 7 ], although the meiotic and developmental competence of metaphase II (MII) oocytes obtained in vitro remains lower compared with that of ovulated MII oocytes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NSN oocytes, as immature GV oocytes, also enter GVBD at almost the same time as SN, hence they are lacking an extent of time during which NSN would have converted to SN in vivo, and this deficit of time results in fewer transcripts accumulated. The poor developmental ability of NSN oocytes is manifested as reduced polar body extrusion and low zygote development rates (Cavalera, Simovic, et al, 2019; Cavalera, Zanoni, et al, 2019), and the fertilized embryos of NSN oocytes often stop developing at the two‐cell stage (Chen et al, 2017). RNA sequencing (RNA‐seq) data of GV oocytes has indicated that SN oocytes possess more transcripts than NSN oocytes (Ma et al, 2013), which is essential for oocyte development, fertilization, and zygote development.…”
Section: Introductionmentioning
confidence: 99%